2018
DOI: 10.1590/0366-69132018643692169
|View full text |Cite
|
Sign up to set email alerts
|

Influência da composição e das variáveis de processamento deformulações à base de argilas - uso em materiais refratários

Abstract: ResumoAs argilas são componentes fundamentais das massas para produção de materiais cerâmicos tradicionais, pois garantem plasticidade na etapa de conformação e resistência mecânica após a queima; também podem ser utilizadas nas formulações de cerâmicas refratárias devido ao desenvolvimento da fase mulita em temperaturas elevadas. O objetivo deste trabalho foi avaliar o efeito da composição, tempo de maturação e temperatura de queima em formulações à base de argilas para uso na fabricação de materiais refratár… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
2
8
0
1
Order By: Relevance
“…This work is consistent with, or explains discrepancies of, a number of former studies that applied different methods (Agrell & Smith, 1960;Cameron, 1977;Ylä -Jä ä ski & Nissen, 1983;Kahn-Harari et al, 1991;King, 2014;Klar et al, 2017). In routine work on mullite using powder diffraction, satellite reflections are not observed and therefore not considered (Ren et al, 2018;Figueiredo et al, 2018;Lerdprom et al, 2018;Ripin et al, 2018;Sacks et al, 1991). Sayir & Farmer (1994) reported on a strong variation in the tensile strength of different samples, with second-order satellites either present or absent, indicating that different degrees of ordering may, to some extent, account for the different properties.…”
Section: Discussionsupporting
confidence: 83%
“…This work is consistent with, or explains discrepancies of, a number of former studies that applied different methods (Agrell & Smith, 1960;Cameron, 1977;Ylä -Jä ä ski & Nissen, 1983;Kahn-Harari et al, 1991;King, 2014;Klar et al, 2017). In routine work on mullite using powder diffraction, satellite reflections are not observed and therefore not considered (Ren et al, 2018;Figueiredo et al, 2018;Lerdprom et al, 2018;Ripin et al, 2018;Sacks et al, 1991). Sayir & Farmer (1994) reported on a strong variation in the tensile strength of different samples, with second-order satellites either present or absent, indicating that different degrees of ordering may, to some extent, account for the different properties.…”
Section: Discussionsupporting
confidence: 83%
“…The principal effect of alkali in clays is to reduce their refractory characteristics. The mineralogical, physical, and thermal characterization of the raw materials and ceramic masses has been shown in another article 7 by the same group.…”
Section: Resultsmentioning
confidence: 95%
“…The processing parameters of ceramics masses containing aluminosilicates have been studied at the Federal University of Campina Grande in recent years, with significant results 6,7 . Figueirêdo et al 7 evaluated some of the processing parameters of clay-based ceramic masses that had been shaped by uniaxial pressing for use in the manufacture of refractory materials. The results showed that the chemical and granulometric composition of the clays, as well as the processing variables, influenced their physical-mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De modo geral, as indústrias de cerâmica tradicional utilizam a argila como matéria-prima principal na fabricação de diversos materiais, tais como: blocos de vedação e estruturais, telhas e tijolos maciços [4]. Entre as diversas matérias primas provenientes da argila têm-se a do tipo caulinita que é composta por alumina e sílica, e quando submetida a altas temperaturas estes óxidos se combinam, influenciando nas propriedades mecânicas do material, como por exemplo a resistência e a absorção de água [5].…”
Section: Introductionunclassified